Employees' perception on current office layout toward productivity at Majlis Daerah Kerian, Parit Buntar / Nur Farhana Ismail - Ismail, Nur Farhana (2015)
The purpose of this research is to identify the employee perception toward current office layout at Majlis Daerah Kenan. This research intended to investigate the current office layout and the future office layout that preferred by employees. The sample size use for this study is 52 and from 60 of populations, only 52 sample size used for the actual survey based Krejcie & Morgan table for determining sample size from a given population. The questionnaire has been distributed to all supports employees in Majlis Daerah Kenan and about 56 respondents have answered the questionnaires distributed. Social Science Software (SPSS) version 22 is used to analyze the results collected. In order to make some improvement to the employees in Majlis Daerah Kerian, some recommendation and recommendation for the future research was stated.